Quantifying energy not served in power capacity expansion planning with intermittent sustainable technologies - Poullikkas, Andreas (My University, 2015)
In this work, estimations are made of the energy not served (ENS) in a power capacity expansion problem in the case of integration of intermittent sustainable technologies. For this purpose, part of the power generation system of the United Arab Emirates (UAE) is examined. Five capacity expansion scenarios using sustainable power generation technologies are investigated, including the integration of carbon capture and storage (CCS) technologies and solar-based power generation systems (intermittent systems as well as dispatchable systems using thermal storage), and compared with the business as usual scenario (BAU) for various natural gas prices. Based on the input data and assumptions made, the results indicate that the BAU scenario is the least cost option. However, if the UAE move towards the use of sustainable power generation technologies in order to reduce carbon dioxide emissions, the most suitable alternative technologies are: (i) natural gas combined cycle technology integrated with CCS systems, and (ii) concentrated solar power systems with 24/7 operation. The other candidate sustainable technologies have a considerable adverse impact on system reliability since their dispatchability is marginal, leading to power interruptions and thus high ENS cost.
Keywords: Energy not served; Cost of electricity; Power system reliability; Power economics; Generation expansion planning